Progress and prospects in the management of kidney stones and developments in phyto-therapeutic modalities. (May 2019) - Akram, Muhammad; Idrees, Muhammad
The aim of this article was to review some of the new and commonly used medicinal plants in the treatment of kidney stones, emphasizing medicinal uses, pharmacological activity, and research study of medicinal plants. Renal stones are a common problem worldwide with substantial morbidities and economic costs. The high economic burden associated with kidney stones is linked mainly with healthcare costs. In vitro and in vivo studies on alternative treatment of kidney stones have been searched by using words such as phytotherapy of kidney stones, medicinal plants used in kidney stones, and lithotriptic activity of plants. Articles reviewed showed that medicinal plants have lithotriptic potential. Medicinal plants may be useful in treatment of kidney stones. This study was aimed to explore and elaborate the efficacy and availability of alternative treatment for kidney stones and to provide safe, cost effective, and efficacious management options as well as reduce the burden of disease. Cost effectiveness may enable improvements in treatment efficiency that can benefit patients and the healthcare system. Further randomized clinical trials should be conducted to evaluate the safety and efficacy of medicinal plants.